The Students' Comprehension On Politeness/ Impoliteness In Interlanguage Pragmatics Of Complaints By Efl Learners In Ums - Perdana, Hestuningtyas Maharani, Agus Wijayanto, Ph.D, Mauly Halwat Hikmat, Ph. D (2017)
Complaint is one of speech acts which potentially insults the communicators, mainly to complainees. Their understanding on politeness and impoliteness in interlanguage pragmatics of complaint is expected to minimize face threatening act and to lose misunderstanding in communication. This research aims to investigate the EFL learners' understanding on politeness and impoliteness in interlanguage pragmatics of complaints. Discourse Completion Tasks (DCT) is choosen as the instrument in collecting data. The writer recruited 25 EFL learners to be respondents in this research. The findings discovered that the EFL learners' understanding on politeness/ impoliteness were not separated from their comprehension on social distance, status level, and imposition degree in their cultural dimension. The social aspects such as pragmalinguistics forms, context situations, and complaineers-complainees' relationship of complaint determine politeness/ impoliteness.